Comparison of neutrophil lymphocyte ratio, platelet lymphocyte ratio, and mean platelet volume and PCR test in COVID-19 patients - Özsari,Süleyman (2021)
SUMMARY OBJECTIVE: The polymerase chain reaction test, used in the diagnosis of COVID-19, can be positive with delay, and thorax tomography is used for the diagnosis of the disease. We aimed to compare the relation between thorax tomography findings, PCR test results, and neutrophil lymphocyte ratio; platelet lymphocyte ratio and mean platelet volume neutrophil lymphocyte ratio; platelet lymphocyte ratio and mean platelet volume in COVID-19 patients. METHODS: COVID-19 patients were divided into three groups, according to baseline laboratory and thorax tomography findings: Group A: thorax tomography finding positive – polymerase chain reaction test positive; Group B: thorax tomography finding negative – polymerase chain reaction test positive; and Group C: thorax tomography finding positive – polymerase chain reaction test negative. Neutrophil lymphocyte ratio, platelet lymphocyte ratio, and mean platelet volume values were compared between these three groups. RESULTS: Group C neutrophil lymphocyte ratio level and polymerase chain reaction level were statistically higher than that of group B (p<0.001 in both). Mean platelet volume was not statistically significant between groups (p>0.005 for all). A positive correlation was detected between neutrophil lymphocyte ratio and C-reactive protein (r=0.421, p<0.001). Similarly, positive correlation was found with polymerase chain reaction and C-reactive protein (r=0.243, p=0.001). CONCLUSIONS: The thorax tomography finding can be detected earlier in the disease before the polymerase chain reaction test. The sensitivity of the polymerase chain reaction test varies according to the tester, the way of performing it, and the quality of the test. Therefore, especially in patients with polymerase chain reaction negative and thorax tomography findings, neutrophil lymphocyte ratio and platelet lymphocyte ratio levels should be evaluated, and patients should be followed up upon suspicion of COVID-19 diagnosis.